Pengaruh Serangan Wormhole terhadap Kinerja Protokol Temporally Ordered Routing Algorithm (TORA) pada Mobile Ad Hoc Network (MANET) - Ravy Agistya Alkamaly; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Mobile Ad-Hoc Network (MANET) is a wireless network that has several interconnected nodes and acts as a router to transmit data. Several nodes can interact with each other by implementing routing protocols, one of which is TORA. TORA has a control message in the form of UDP (Update) to update the routing table and a CRL (Clear) control message that can minimize the occurrence of continuous looping which results in data not reaching its destination. The minimization process is not said to be perfect if there are many additional nodes. Research needs to be done using other methods, namely manipulating control traffic on the network by adding attacks in the form of wormhole attacks. Wormhole has characteristics that are very likely to affect the environmental conditions of MANET using TORA. The characteristics possessed by Wormhole are 2 nodes that can be connected to each other and can send data even with a very far position so that it is likely to reduce the occurrence of looping during packet transmission. The test results are obtained based on the Packet Delivery Ratio, Packet Loss, Troughput, and End to End Delay test parameters. Overall, the application of wormhole in TORA produces better performance compared to not applying wormhole. Packet delivery ratio testing with a scenario of 20 nodes shows 90.56% results compared to only 79.64% without wormhole. Testing the average troughput with a scenario of 20 nodes shows results of 95.06kbps compared to only 83.6kbps without wormhole. And testing the average end to end delay with a scenario of as many as 20 nodes shows results of only 19.18ms compared to without a wormhole rising to 30.12ms.